Actively Involving Students With Learning Disabilities in Progress Monitoring Practices. (May 2022) - Furey, Jenlyn; Loftus-Rattan, Susan M.
Academic progress monitoring is essential when implementing Individualized Education Programs for students with learning disabilities and more generally in a multi-tiered system of supports framework. Although students' progress is monitored frequently in schools today, these students often are not actively involved in this practice. Research has shown that actively involving students in progress monitoring through performance feedback and goal setting can lead to improved academic and motivational outcomes. This column describes a progress-monitoring performance feedback and goal-setting routine that supplements typical academic progress-monitoring practices. The ways in which the routine aligns with evidence-based practices to improve student outcomes in reading, writing, mathematics, and academic motivation are discussed. Step-by-step guidance, examples, and resources are provided to support practitioner implementation. Resources for evaluating outcomes are described.